2001
DOI: 10.1063/1.1339254
|View full text |Cite
|
Sign up to set email alerts
|

Raman-spectroscopic evaluation of the long-range order in Ba(B1/3′B2/3″)O3 ceramics

Abstract: Ordered Ba(B1/3′B2/3″)O3 ceramics are currently used as dielectric resonators for microwave and millimeter wave technologies. The degree of ordering is generally determined by x-ray techniques. In this work, we demonstrate that Raman spectroscopy can be used to evaluate the degree of long-range order of these materials. We also show how varying the degree of order of samples allows partial assignment of the optical vibrational modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 9 publications
6
63
1
1
Order By: Relevance
“…While the Raman-active modes are only due to vibrations of Ba and O atoms (A g , B g and E g ), the infrared active phonons include the vibrations of ions in the B-sites (Y C3 and Nb C5 ions for A u and E u vibrational modes). 2,4,5 However, for complex perovskites with 1 : 1 ordering, infrared measurements fail to study crystal structures because of the proximity of transverse and longitudinal phonons, which makes difficult the identification and assignment of the modes. 2 Micro-Raman spectroscopic investigations were carried out in samples fired in temperatures ranging from 600 to 1600°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the Raman-active modes are only due to vibrations of Ba and O atoms (A g , B g and E g ), the infrared active phonons include the vibrations of ions in the B-sites (Y C3 and Nb C5 ions for A u and E u vibrational modes). 2,4,5 However, for complex perovskites with 1 : 1 ordering, infrared measurements fail to study crystal structures because of the proximity of transverse and longitudinal phonons, which makes difficult the identification and assignment of the modes. 2 Micro-Raman spectroscopic investigations were carried out in samples fired in temperatures ranging from 600 to 1600°C.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the microwave hydrothermal BYN, as previously discussed by our research group in recent publications. 2,4,5,12 It was observed that BYN samples fired at lower temperatures exhibited a higher number of broader phonon modes, which could be due to lattice distortions indicating lower-symmetry structures. Thus, for samples fired at temperatures lower than 1600°C, 1 95 3 102 3 1 95 13 2 299 35 305 57 2 124 26 3 372 6 380 7 3 146 43 4 426 21 434 36 4 211 87 5 534 18 537 23 5 284 76 6 716 25 716 30 6 337 49 7 734 22 743 26 7 373 31 8 800 10 809 12 8 417 27 9 837 22 843 27 9 533 107 10 614 78 11 771 69 12 812 42 a careful analysis was conducted to examine the possible origins for the observed behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In other cases, a doubling of bands, originating from vibrational modes involving vibrations of those atoms which occupy the same crystallographic sites, can be observed (two-mode behaviour). 11,13 Recently, a third possibility has been proposed, i.e. it has been shown that the spectra of disordered crystals can be explained in some cases considering a symmetry breakdown due to cation disorder.…”
Section: Discussionmentioning
confidence: 99%
“…30 37 Tais defeitos quebram localmente a simetria da estrutura, permitindo o surgimento de bandas silenciosas e/ou infravermelho ativas no espectro Raman. 13 A completa distribuição dos modos vibracionais, segundo a análise do grupo fator, para cada uma das estruturas cristalinas supracitadas é resumida na Tabela 3. Cúbico:…”
Section: -29unclassified